PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Hutasoit, Sri Anjeli; Maidani, Maidani; Khasanah, Uswatun (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to assess the impact of dividend policy, debt policy, and investment decisions on the value of a company in the manufacturing sector that focuses on food and beverages listed on the Indonesia Stock Exchange (IDX) during 2022 to 2024.In this study, company value is measured by Price to Book Value (PBV), while dividend policy uses the Dividend Payout Ratio (DPR), policy uses the Debt to Equity Ratio (DER), and investment decisions are measured through the Price Earning Ratio (PER).The method used in this study is a quantitative approach with multiple linear regression analysis. The research sample was taken using SPSS, which resulted in 20 eligible companies. Data were collected from the company's annual financial reports published on the official website of the Indonesia Stock Exchange.